2017
DOI: 10.1007/s10067-017-3746-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-6 expression on THP-1 by IL-34 stimulation up-regulated rheumatoid arthritis Th17 cells

Abstract: IL-34 is a pleiotropic cytokine, which is a key regulator of monocytes/macrophages and might participate in the pathogenesis of RA. In this study, we aimed to explore the effect of IL-34 on the monocyte-like cell line THP-1 and the quantitative variation of Th17 cells in THP-1 and RA CD4T cells coculture system. CD4T cells were purified from RA PBMC using immunomagnetic beads. THP-1 were cultured with RA CD4T cells. The frequency of Th17 cells was determined by FACS. Fluorscence indensity and expression of ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
See 3 more Smart Citations
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
“…Pro‐inflammatory cytokines are fundamental to the pathophysiology of RA. Numerous studies have unveiled the pathologic role of IL‐34 in RA as a downstream effector of pro‐inflammatory cytokines, contributing importantly to inflammation and bone erosion . Elevated levels of IL‐34 can be detected in the blood, synovial fluids, and synovial tissues of RA patients.…”
Section: Pathological Roles Of Il‐34mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-34 can induce the differentiation, proliferation, and infiltration of macrophages in the inflamed synovia, which are the central immune cells in RA pathogenesis 31,32,36. It also stimulates IL-17-producing Th17 cells, which are the crucial drivers of autoimmune tissue injury in RA 38-40. Furthermore, overexpression of IL-17 is implicated in RA etiology.…”
Section: Il-34 In Autoimmune Diseasesmentioning
confidence: 99%